Prevalensi Penggunaan Fall Risk Medicine pada Pasien Lanjut Usia di Instalasi Rawat Jalan Rumah Sakit Madiun - Fita Rahmawati; Nasikhatul Mustafidah; Lily Annisa (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The use of certain drugs is known to be an extrinsic factor the risk of falling in the elderly (elderly) because it can cause postural hypotension, sedation, dizziness, weakness, drowsiness, muscle weakness, and other side effects. This study aims to determine the profile of drug use that have the potential to fall in the elderly. This study used a cross-sectional descriptive design with purposive sampling technique. The study was carried out at two regional hospitals in Madiun (RSUD Dr. Soedono Madiun and RSUD Kota Madiun). The data is sourced from the outpatient's medical record of Neurology and Internal Medicine clinics and from the medication record in the Pharmacy Installation from May to October 2018. The results showed that there were 343 patients (64.11%) out of 535 patients involved in the study using fall risk medicines (FRM). Three FRM groups that were often prescribed were antihypertensive 52.71% (282 patients), anticonvulsants 20.19% (108 patients), and benzodiazepines 10.47% (56 patients). A number of 46.54% (249 patients) used FRM included in the low-risk category (Medication Fall Risk Score 1-5), and as many as 17.57% (94 patients) were included in high risk (Medication Fall Risk Score ≥ 6). The elderly that use 1 FRM was 24.86% (133 patients), followed by 2 drugs was 19.07% (102 patients). The results of this study realized that the use of fall risk medicines in the elderly is quite high, so it is necessary to weigh the risks and benefits of its use to prevent falls in the elderly.